Pure Red Cell Aplasia due to B19 Parvovirus Infection after Autologous Stem Cell Transplantation. (27th June 2011) - Tsirigotis, Panagiotis; Girkas, Konstantinos; Economopoulou, Christina; Bouchla, Anthoula; Papanicolaou, Nikolaos; Economopoulou, Panagiota; Papageorgiou, Sotirios; Pappa, Vassiliki; Dervenoulas, John
Abstract : Parvovirus B19 is recognized as a rare cause of pure red cell aplasia (PRCA) in allogeneic stem cell (SCT) and solid organ transplant patients. We report a patient with Hodgkin's disease who developed PRCA due to parvovirus B19 after autologous SCT and who had an excellent response after treatment with gamma-globulin.